(untitled) - Williams, Marcia L; Covington, Barbara (Thousand Oaks, Calif., 1999)
Includes bibliographical references (p. 157-159) and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Distance education -- Methods -- United States; Telecommunication in education; Giáo dục từ xa -- Phương pháp -- Hoa Kỳ